1986
DOI: 10.1295/polymj.18.1037
|View full text |Cite
|
Sign up to set email alerts
|

Living and Highly Isotactic Polymerization of Methyl Methacrylate by t-C4H9MgBr in Toluene

Abstract: ABSTRACT:Highly isotactic PMMAs with narrow molecular weight distribution (Mwl M. < 1.2) have been prepared by the polymerization of MMA in toluene at -78oC initiated by t-C 4 H 9 MgBr prepared in diethyl ether. The polymerization proceeded in a "living" manner, in which the initiation reaction was fast and quantitative whereas the propagation was slow. The ether solution of t-C4 H9MgBr used as the initiator contained almost equal amounts of MgBr2 produced by an Wurtz type coupling during the preparation. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
125
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 16 publications
2
125
1
2
Order By: Relevance
“…12,13 Following this finding, we also reported several stereospecific living polymerizations of methacrylates; syndiotactic-specific one with tert-butyllithium (tBuLi)/tributylaluminum (n-Bu 3 Al), 14,15 and heterotactic-specific one with t-BuLi and bis(2,6-di-tert-butylphenoxy)methylaluminum [MeAl(ODBP) 2 ]. [16][17][18][19][20][21][22][23][24] More recently, the authors have reported that t-BuLi/bis(2,6-di-tert-butylphenoxy)ethylaluminum [EtAl(ODBP) 2 ] initiating system was effective for stereospecific living polymerization of methacrylates, 20 acrylates 25 and methyl bicyclobutane-1-carboxylate.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…12,13 Following this finding, we also reported several stereospecific living polymerizations of methacrylates; syndiotactic-specific one with tert-butyllithium (tBuLi)/tributylaluminum (n-Bu 3 Al), 14,15 and heterotactic-specific one with t-BuLi and bis(2,6-di-tert-butylphenoxy)methylaluminum [MeAl(ODBP) 2 ]. [16][17][18][19][20][21][22][23][24] More recently, the authors have reported that t-BuLi/bis(2,6-di-tert-butylphenoxy)ethylaluminum [EtAl(ODBP) 2 ] initiating system was effective for stereospecific living polymerization of methacrylates, 20 acrylates 25 and methyl bicyclobutane-1-carboxylate.…”
mentioning
confidence: 80%
“…In order to confirm this assumption, 13 C NMR experiments of these initiator solutions were carried out in toluene-d 8 at À78 C (Figure 1). In the 13 C NMR spectrum of BnTMSNLi itself showed two sets of distinguishable signals.…”
Section: Identification Of N-benzylmethacrylamidementioning
confidence: 96%
See 2 more Smart Citations
“…terr-Butylmagnesium bromide may be used to synthesize highly isotactic PMMA in noncoordinating solvents at low temperatures (44)(45)(46). TTie unusual control imparted by this reagent is thought to arise from an interaction between the initiating species, which has been postulated to exist as a complex aggregate bearing multiple tert-butyl groups due to the Schlenk equilibrium, and the active endgroup (47).…”
Section: Strategies For Living Polymerizationmentioning
confidence: 99%